Retroperitoneal Leiomyosarcoma: A Case Report - Banu, Nasima Arjumand; Akter, Sayeda Husna; Talukdar, Rezaur Rahman; Banu, Nahida Arjumand; Islam, Nasim Imtiaz (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 229-234 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15364